Bird's engineering mathematics - Bird, J. O. (Routledge, 2021)
"Mathematics is explained using over 550 practical engineering worked examples and interactive problems, for Level 2 and 3 engineering and A level courses. The companion website provides essential formulae, multiple choice tests, and full solutions for 1,900 further questions; and answers to revision tests for adopting course instructors"--